Pengaruh Segmenting Targeting Positioning (STP) Terhadap Kepuasan Konsumen H-37 Adventure Yogyakarta - Sahvira Apriliana; Bangun Putra Prasetya (Journal of Management and Creative Business, 2024)
There is a lot of interest in young people and old people who want to rent camping equipment and rent outdoor tents nowadays. This fact is a great opportunity for H-37 Adventure to start this Outdoor Equipment Rental business. Research Approach, Population, Sample and Sampling Techniques, Data and Data Sources, Data Collection Techniques, Data Analysis Techniques From table 1 it can be seen that the correlation of each item is with the total score of each question for the Segmenting (X1), Targeting variables (X2), Positioning (X3), and Consumer Satisfaction (Y), all produce a Pearson correlation above 0.30 with a significant value of less than 0.005. Thus, all of the research variable question items are valid. From the results of the discussion the following conclusions are drawn: 1. Together/simultaneously segmenting, targeting and positioning have a significant effect on consumer satisfaction. 2. Partially, segmenting has no or no significant effect on consumer satisfaction at H-37 Adventure Yogyakarta. 3. Partially targeting has an influence or significance on consumer satisfaction at H-37 Adventure Yogyakarta. 4. Partially, positioning has an influence or significance on consumer satisfaction at H-37 Adventure Yogyakarta.